The genera Agathocles and Surenus (Hemiptera: Heteroptera: Pentatomidae): tribal reassessment, redescription, new synonyms, and description of two new species - Salini, S.; Kment, Petr (Zootaxa, 2021)
The genus Surenus Distant, 1901 (Hemiptera: Heteroptera: Pentatomoidea: Pentatomidae: Pentatominae: Halyini) is revisited and found to be a junior subjective synonym of the genus Agathocles Stål, 1876 (currently Pentatominae: Rolstoniellini). The genus Agathocles and its type species, Agathocles limbatus Stål, 1876, are redescribed. Lectotype of Surenus normalis Distant, 1901 (= Agathocles normalis (Distant, 1901) comb. nov.) is designated and the unknown male of the species is described. Agathocles yunnanensis Zhang & Lin, 1984, syn. nov., is considered junior subjective synonym of A. limbatus. Two new species are described: Agathocles flavipes sp. nov. from India (Andhra Pradesh, Karnataka, Maharashtra, and Tamil Nadu) and A. joceliae sp. nov. from Malaysia (Kelantan, Perak). The new species differ from their congeners mainly by the morphology of mandibular plates, length of antennomeres I, IIa and IIb, body length, and structure of male genitalia. Agathocles dubius Distant, 1921 is transferred to the genus Caystrus Stål, 1861 (Pentatominae: Caystrini) based on examination of its holotype with the resulting new combination: Caystrus dubius (Distant, 1921), comb. nov. One new combination is proposed, Paramecocoris ruficornis (Fieber, 1851), comb. nov. (from preoccupied Paramecus Fieber, 1851), and its type locality is clarified as Tenasserim (south Myanmar). Gender agreement and authorship of the name Riazocoris niger Ahmad & Afzal, 1977 in Ahmad et al. (1977: 161) are corrected and status of its name bearing type is clarified as lectotype. The following new distribution records are given: A. limbatus from Cambodia, China (Guangxi, Tibet), Laos and Thailand, A. normalis, Caystrus obscurus (Distant, 1901a) and Critheus lineatifrons Stål, 1869 from Laos, Amasenus corticalis Stål, 1863 from Cambodia, Indonesia (E Kalimantan), Laos, Myanmar and Thailand, and Rolstoniellus boutanicus (Dallas, 1849) from Vietnam. Based on characters of external morphology and genitalia, the genus Agathocles is compared with representatives of the genera Halys Fabricius, 1803 (Halyini), Caystrus (Caystrini), Laprius Stål, 1861 (Myrocheini), and Exithemus Distant, 1902 (currently in Rolstoniellini). As a result, the genus Agathocles is here transferred to the tribe Caystrini. The genus Kyrtalus Van Duzee, 1929 is tentatively placed in Myrocheini based on the presence of sulcate mesosternum and femora provided with teeth.